Canadian income tax law - Duff, David (LexisNexis Canada, 2023)
"Canadian Income Tax Law provides readers with an overview of the foundations of tax law, including critical cases and expert commentary. Introductory chapters provide a foundation for the study of statutory provisions and judicial decisions, including up-to-date caselaw and analysis; the remaining chapters follow the structure of the Income Tax Act."– Provided by publisher.